Development of a web-based mobile robots tracking system - Tern, Tien Siew. (2009)
This project report will discuss the development of a web-based mobile robots tracking system. The users are able to monitor the status of the robots through the internet. The website is created using Java Server Pages and the data to be displayed on the webpage is stored in the MySQL database. An algorithm on how to handle the incoming data to be used to update the database will be explained in detail. NetBeans program is used to read the input files and create SQL statements in the output files. The output files are then used for updating the database.